Highly enhanced transverse plasmon resonance and tunable double Fano resonances in gold@titania nanorods. Issue 12 (3rd March 2016) - Ruan, Qifeng; Fang, Caihong; Jiang, Ruibin; Jia, Henglei; Lai, Yunhe; Wang, Jianfang; Lin, Hai-Qing
Abstract : Au@TiO2 nanorods are synthesized and found to possess similarly strong transverse and longitudinal plasmon resonances and exhibit double Fano resonances. Abstract : Gold nanorods have attracted intensive interest owing to their localized surface plasmon resonance properties and enormous potential applications. The transverse plasmon of Au nanorods is usually weaker than the longitudinal one, hampering certain plasmonic applications. Herein we report on the intensification of the transverse plasmon resonance by coating TiO2 onto Au nanorods. The transverse plasmon mode of the resultant Au@TiO2 nanorods with a sufficiently thick shell can be comparable to or even stronger than the longitudinal one in intensity. Moreover, both the transverse and longitudinal plasmon resonances of the Au@TiO2 nanorods exhibit an asymmetric line shape on their scattering spectra. Electrodynamic simulations and analyses based on a coupled oscillator model suggest that the asymmetric line shape originates from the coupling between the Au core and TiO2 shell. Apart from the shell thickness, the plasmonic properties of the Au@TiO2 nanorods can also be tuned by the dimension of the Au nanorod core. In addition, the polarization-dependent light scattering from the individual Au@TiO2 nanorods has also been investigated. These results will be of high importance for understanding the interactions between noble metals and semiconductors in plasmonic hybrid nanosystems, and for designing novel plasmonic nanostructures with desired optical properties and functions.